COMMUNICATIVE LANGUAGE TEACHING: HOW IS IT REALIZED IN THE CLASSROOM? - Katharina Rustipa (Dinamika Bahasa dan Budaya, 2011)
Communicative language teaching is aimed at enabling learners to communicate in the target language. It is a replacement of audio-lingual or grammar translation that is justified unable to make the learners to communicate in the target language. The communicative approach has dominated English language teaching worldwide. Language was no longer seen as abstract grammatical rules, but of having applications in social contexts. There is a change of role of the teacher and the students. Formerly, the teachers play a role as a model. Today, with the communicative methodology, he has new roles as facilitators and monitors. The students must take part actively in the classroom activities which are designed to make the students interact each others. Key words: CLT, CBI, TBI, communicative competence, fluency, accuracy, facilitator, monitor, language function, speculation, jigsaw/sequencing, ranking & rating, matching